Archival Analysis in the Service Section Karawang Pratama Tax Service Office - Naga Bintang Pramesti; Eka Yulyana; Mochamad Faizal Rizki (Jurnal Ilmiah Wahana Pendidikan, 2022)
Archives are very important, so their management is very important to pay attention to. many companies pay less attention to the arrangement of archives, we can see this from the arrangement of company archives that accumulate in warehouses or are not maintained so that it is difficult to find them again if needed. One of them is the Karawang Pratama Tax Service Office. Taxes are a primary business that continues to be carried out every time, the impact is that there are many archives that need to be managed. Therefore, archives clearly play an important role in an organization or company. Because without archives it is impossible for someone to be able to remember all the documents and records that are so complex in managing company files. Archives that are well organized, orderly and orderly are a must for the smooth storage of documents in the presentation of information. The research method in this study used a descriptive method with a qualitative research approach, namely a study that aims to provide an overview of how archives are in the service section of KPP Pratama Karawang.